Molecular approach for enhancing phosphate uptake in oil palm - Ijab, S. M.; Abdullah, Siti Nor Akmar; Ahmadi, F.; Kadkhodaei, S. (Faculty of Engineering, Universiti Putra Malaysia, 2016)
Oil palm is grown in acidic tropical soils with low bioavailability of inorganic phosphate (orthophosphate; Pi), the form that can be assimilated by plant. An understanding on the molecular mechanism for acquiring Pi by oil palm roots under Pi deficient condition may help to enhance oil palm productivity and reduce excessive input of fertilizer. A high-affinity and energy-mediated co-transport system is believed to be the major system responsible for uptake of Pi from soil into the root cells against a steep concentration gradient. This paper reports on the characterization of an oil palm gene encoding a high affinity phosphate transporter designated as EgPHT1. The deduced protein sequence of the EgPHT1 cDNA specifically expressed under Pi starvation condition indicates that it is a plasma membrane localized protein containing 12 trans-membrane spanning domains. Among the regulatory motifs identified in the promoter sequence includes several root-specific, phosphate starvation inducible, water stress-responsive and hormone signaling elements. Functional study using β-glucuronidase reporter gene showed that EgPHT1 promoter can drive root-specific and phosphate starvation-inducible expression in transiently transformed tissues of the monocotyledonous oil palm as well as in stably transformed dicotyledonous model plant, Arabidopsis thaliana. The potential application of the information generated on improving Pi uptake by oil palm will be discussed.